Morphological Characteristics of Male Genitalia in Some Species in the Genus Torymus (Torymidae, Hymenoptera) - Klymenko, S.I. (Вестник зоологии, 2012)
Впервые исследована морфология генитального аппарата самцов некоторых видов рода Torymus. В отличие от генитального аппарата эвритомид как признака, который является высоко видоспецифическим, в строении гениталий торимид нет четко выраженных видовых отличий: фаллобаза у всех исследованных видов открытого типа, у большинства видов по три крючка на дигитальных склеритах, в основании крючьев имеются небольшие зубцы. Morphology of male genitalia in some species in the genus Torymus Dalman is studied for the first time. In contrast to genitalia of Eurytomidae species, where this structure is highly species-specific, the structure of genitalia in Torymidae species show no distinct specific differences: phallobase in studied species is opened; most species have three hooks on digital sclerites with the small indents at their bases.